Effects of Fatty Acid Oxidation and Its Regulation on Dendritic Cell-Mediated Immune Responses in Allergies: An Immunometabolism Perspective. (12th August 2021) - Sun, Shanfeng; Gu, Yanjun; Wang, Junjuan; Chen, Cheng; Han, Shiwen; Che, Huilian
Abstract : Type 1 allergies, involve a complex interaction between dendritic cells and other immune cells, are pathological type 2 inflammatory immune responses against harmless allergens. Activated dendritic cells undergo extensive phenotypic and functional changes to exert their functions. The activation, differentiation, proliferation, migration, and mounting of effector reactions require metabolic reprogramming. Dendritic cells are important upstream mediators of allergic responses and are therefore an important effector of allergies. Hence, a better understanding of the underlying metabolic mechanisms of functional changes that promote allergic responses of dendritic cells could improve the prevention and treatment of allergies. Metabolic changes related to dendritic cell activation have been extensively studied. This review briefly outlines the basis of fatty acid oxidation and its association with dendritic cell immune responses. The relationship between immune metabolism and effector function of dendritic cells related to allergic diseases can better explain the induction and maintenance of allergic responses. Further investigations are warranted to improve our understanding of disease pathology and enable new treatment strategies.